SISTEM INFORMASI PENDAFTARAN SANTRI DAN SANTRIWATI BARU PONDOK PESANTREN TEBUIRENG - , M MACHBUB MARZUQI; , Muh. Fakhrurrifqi, S.Kom., M.Cs. ([Yogyakarta] : Universitas Gadjah Mada, 2014)
Registration is one of the most important elements in the education system. To produce quality of students and female students are required to improve education quality, one of which improve services of registration process. In educational process, registration process needs to be selected very detailed and precise to determine the prospective students and female students who qualify. Development of information systems students and female students enrollment Tebuireng Boarding School has function to find prospective students and female students who have the best value and the best test results, the information system is built using the programming language PHP, CodeIgniter framework, MySQL database, and Twitter Bootstrap of manufacturing interface. This information system provides the services such as news data management, registrant data management, agenda data management, education unit of data management, and registrant data management that displayed in graphic form, the registrant data printing. This information system is expected to facilitate the registration process and the process of selecting applicants, and provide the results of data registries quickly.